2004
DOI: 10.1002/jnr.20326
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C uptake and recycling among normal and tumor cells from the central nervous system

Abstract: Specialized cells transport vitamin C in its reduced form using sodium-dependent cotransporters (SVCT1 and SVCT2). Additionally, different cells transport the oxidized form of vitamin C, dehydroascorbic acid, through glucose transporters (GLUTs). We have proposed recently a model for vitamin C uptake that resolves the apparent contradiction that although only ascorbic acid is detectable in vivo, there are cells that transport only dehydroascorbic acid. We carried out a detailed kinetic analysis to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 66 publications
8
59
0
Order By: Relevance
“…In agreement with previous in situ hybridization (Astuya et al, 2005;García et al, 2005) and immunocytochemical studies, the SVCT2 was not present in endothelial cells lining cortical capillaries in the mouse, either by direct staining or by immunoblotting. However, when the cells were purified and placed into culture, the SVCT2 was readily detected after several days and was associated with ascorbate transport rates comparable to immortalized endothelial cell lines.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous in situ hybridization (Astuya et al, 2005;García et al, 2005) and immunocytochemical studies, the SVCT2 was not present in endothelial cells lining cortical capillaries in the mouse, either by direct staining or by immunoblotting. However, when the cells were purified and placed into culture, the SVCT2 was readily detected after several days and was associated with ascorbate transport rates comparable to immortalized endothelial cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous in situ hybridization (Astuya et al, 2005;García et al, 2005) and immunocytochemical studies, the SVCT2 was not present in endothelial cells lining cortical capillaries in the mouse, either by direct staining or by immunoblotting.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have demonstrated that neuronal intracellular ascorbic acid inhibits glucose utilization in neurons (Castro et al, 2009) through GLUT3 inhibition (Figure 8, Beltrán et al, 2011). This mechanism is supported by the idea of ascorbic acid recycling in brain (see above, Figure 10, Astuya et al, 2005). Using primary cultures of cortical neurons treated with a specific shRNA (to block GLUT3 expression) and a fluorescent glucose analogue, we have shown that this transporter is important, using real-time experiments (Figure 7).…”
Section: Neuron-glia Metabolic Couplingsupporting
confidence: 53%
“…Reduction is mainly an enzymatically catalyzed reaction, which may be glutathione-dependent (Ishikawa et al 1998). Astrocytes are thought to be involved in ascorbic acid recycling (Figure 10, Astuya et al 2005). During synaptic activity, ascorbic acid is released from intracellular reservoirs (O'Neill et al ,1984;Ghasemzadeh et al, 1991;Yusa, 2001).…”
Section: Metabolic Activation In Astrocytesmentioning
confidence: 99%